The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0182823
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of photocatalytic potentiality and determination of ecotoxicity (using plant model for better environmental applicability) of synthesized copper, copper oxide and copper-doped zinc oxide nanoparticles

Abstract: NPs synthesis, characterization and azo-dye degradationA facile cost effective wet chemical method of synthesis is proposed for Cu-NPs, CuO-NPs and Cu-doped ZnO-NPs. The nanomaterials are opto-physically characterized for nano standard quality. Cu-doped ZnO-NPs based catalytic system is found to possess most efficient photocatalytic activity in degradation of two organic azo-dyes namely methyl red (MR) and malachite green (MG) that are released as industrial effluents in eco-environment intercollegium. Two pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In this study, we considered ZnO nanoparticles used as antimicrobial agents to fight plant diseases. , The ZnO nanoparticles were observed to be highly dispersed in HRTEM images. High magnification images demonstrate individual particles that are approximately spherical and whose average size is ∼2 nm or less (Figures a,b).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we considered ZnO nanoparticles used as antimicrobial agents to fight plant diseases. , The ZnO nanoparticles were observed to be highly dispersed in HRTEM images. High magnification images demonstrate individual particles that are approximately spherical and whose average size is ∼2 nm or less (Figures a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies displayed that the RAPD assay is effective in evaluating the preliminary toxic effects on plants [43]. Recently, a large number of studies on genotoxicity caused by NPs in crop plants have been widely reported [32,[44][45][46]. The appearance of new DNA bands (n = 6) could be described as mutations, whereas the absence of normal DNA bands (n = 2) is possibly characterized as DNA disintegration or rearrangements of genetic materials [7] caused by iron oxide NP oxidative stress-induced genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Such effect is the primary indication of toxicity in the cellular system. Engineered NPs are reported to exert both positive (Hojjat and Hojjat 2015) as well as negative (Lee et al 2010;Ma et al 2010;Kumbhakar et al 2016;Das et al 2017) effects on the said physiological attributes in higher plants. Negative effects of NPs on the physiological attributes are the consequences of NP-mediated up-regulating stress-responsive gene expression (Khodakovskaya et al 2009).…”
Section: Seed Germination and Seedling Growthmentioning
confidence: 99%